Monument 14 - Laybourne, Emmy. (New York : Feiwel and Friends, 2012)
Trapped inside a chain superstore by an apocalyptic sequence of natural and human disasters, six high school kids from various popular and unpopular social groups struggle for survival while protecting a group of younger children.
Maps on endpapers.
Keywords: Survival -- Juvenile fiction; Teenagers -- Juvenile fiction; Natural disasters -- Juvenile fiction; Cliques (Sociology) -- Juvenile fiction; Survival -- Fiction; Teenagers -- Fiction